Advertisement Strategy using Semiotics as Marketing Approach: An Analysis on Food Product - Soegoto, E S; Albar, C N; Aisyah, M; Luckyardi, S (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The aim of this study is to analyze and discover the effective advertisement strategy using semiotics approach and marketing review. This study used mixed method, which is the combination of quantitative and qualitative method. Questionnaire was used as the data collection method and supported by literature review. The questionnaire was distributed to 100 respondents in Bandung. The questionnaire regarding food advertisement was distributed to students as the study case. The results of this study showed that semiotics could maximize elements of an advertisement and have great effect in conveying the message which makes more potential consumers recognize and attracted to the product. This study concludes that food advertisements can attract more potential consumers if they focus more on the visual element. This study is expected to help food sellers in gaining more potential consumers which indirectly could increase the acquired income.